In the land of exchangers and hunters. An approach to the petroglyphs meaning of the Arawak Subandean complex in the Tambo River - Rojas Zolezzi, Enrique (2022)
What place does the petroglyphs have in the social dynamic of the peoples of the sub-andean arawak ensemble? What is the meaning addressed by them to these designs made in an no determined period of time on that rocks? To answer this questions the author of the present article compare petroglyphs in different places of the ashaninka and matsigenka territory, he compare them with the symbolism of the contemporary paintings on cloth of this populations, and establishes relations between the local fauna represented and the myths about it. He arrives to the conclusion that the Tambo river petroglyphs are an expression of two of the main values of the populations of the sub-andean arawak ensemble: exchange and hunting.